Effects of collagenase incubation time on the isolation of stromal vascular fraction and viability of mesenchymal stem cells - Tran, Trung Kien; Vu, Thi Tien; Dinh, Ho Thao An; Tran, Thu Hang; Nguyen, Trung Nam; Tran, Trung Thanh (Vietnam Journal of Biotechnology, 2025)
There are three groups of potential stem cells that are widely used in regenerative medicine in clinical practice: hematopoietic stem cells, mesenchymal stem cells, and epithelial stem cells. Among them, adipose-derived mesenchymal stem cells (ASCs) are very common in the human body and can be easily obtained without causing major damage to the body. The use of human adipose-derived stromal vascular fraction (SVF) therapy has increased in recent years. SVF is a rich source of mesenchymal stem cells (MSCs) used in regenerative medicine. This study evaluated the effect of collagenase incubation time on the efficiency of SVF isolation and MSC viability. The aim of the study was to optimize the SVF isolation time to obtain MSCs with a high survival rate in clinical applications while ensuring the stemness and differentiation ability of MSCs after isolation. Collagenase digestion at different time points (60, 120, and 180 minutes) was compared, measuring MSC yield and viability via flow cytometry and differentiation assays. Results indicated that 120 minutes of collagenase treatment provided optimal MSC yield and cell viability, demonstrating significant differentiation potential, making this time point ideal for clinical applications.